Marketing Communications Mix Practices Among Micro and Small-Scale Enterprises - Urbiztondo, Marge Ethan A (UI Scholars Hub, 2025)
Research Aims: In developing and emerging economies, MSMEs are pivotal in generating income and fostering economic growth. However, in regions like Mindanao Island, Philippines, there are significant challenges to fostering equitable MSME-induced growth. This study delves into practices related to the marketing communications mix among micro and small enterprises in this region. Design/Methodology/Approach: A mixed-methods approach is used, including quantitative analysis of the marketing communications mix practices among MSMEs, as well as qualitative analysis of interviews with micro and small enterprise owners. Research Findings: The study reveals a significant difference between advertising assessments grouped according to years of operations, classification, nature, form of business, and the frequency of marketing communication. It also shows no significant difference in sales promotions, direct marketing, personal selling, and public relations when grouped according to profile. Theoretical Contribution/Originality: In business classification, hybrid businesses are categorised into more than one type of business. Hence, the assessments in this study provide insights into the marketing communications mix practices of hybrid businesses in the context of MSMEs. Managerial Implications in the South East Asian Context: The findings of the study offer valuable insights into the context of MSMEs in Southeast Asia, which can help rural businesses to strategise for sustainability and contribute to developing MSMEs by incorporating modern marketing practices and adapting technologies to enhance engagement and business growth. Research Limitation & Implications: Limitations include the minimal consideration of external factors that influence the adoption of marketing practices, the study scope, and the study's limited study participants, which are businesses operating for more than one year.